Effect of maternal factors on nutritional status of 1-5-year-old children in urban slum population - Mittal A; Ahluwalia S; Singh J (Wolters Kluwer Medknow Publications, 2007)
Objective: To study the effect of various maternal factors on the prevalence of underweight and stunting among 1-5-year-old children in urban slum population. Design: Cross-sectional study. Materials and Methods: The study was carried out in three urban slums of Tripuri Town, Patiala. All 1-5-year children living in these slums were included, whose mother′s demographic profile, weight and height were recorded. Results: Out of 482 children who participated in the study, 185 (38.38%) had low weight for age whereas 222 (46.06%) had low height for age. Both kinds of malnutrition were common in females than in males. Prevalence of malnutrition was more where mother′s age was less than 20 years. Children of educated mothers were better nourished as compared to illiterate ones. Conclusion: Maternal factors significantly affect a child′s nutritional status, thus encouraging the improvement in the social status of women so as to have healthy children and thereby a healthy future.